The oxidation of low-density lipoprotein (LDL) is believed to be the initiating factor for the development and progression of atherosclerosis. Curcuminoid, the metabolite of Zingiberaceae family such as temu mangga (Curcuma mangga), has been shown to reduce the susceptibility of LDL to oxidation. In this study, we examined the effect of curcuminoid extracted from temu mangga on copper ion-induced lipid peroxidation of low density lipoprotein (LDL) in mice’s macrophages and Macaca nemestrina’s m - Trini i Susmiat; Sulistiyani .; Dondin Sajuthi; Latifah K. Darusman (Forum Pasca Sarjana, 2010)
The oxidation of low-density lipoprotein (LDL) is believed to be the initiating factor for the development and progression of atherosclerosis.  Curcuminoid, the metabolite of Zingiberaceae family such as temu mangga (Curcuma mangga), has been shown to reduce the susceptibility of LDL to oxidation. In this study, we examined the effect of curcuminoid extracted from temu mangga on copper ion-induced lipid peroxidation of low density lipoprotein (LDL) in mice’s macrophages and Macaca nemestrina’s monocytes.  Analyses were done by measuring the formation of thiobarbituric acid reactive substance (TBARS) as malonaldehyde (MDA).  LDL were harvested and isolated from 5 adult female Macaca fascicularis  fed aterogenic diet for 3 months.  LDL oxidation by mice macrophage incubated for 4 hours were inhibited by curcuminoid at concentration of 8 ppm.  There was decreased 17% (P<0.01) in the concentration of MDA compared to control without curcuminoid (31.99B±0. vs 36.77A±0.9 nmol/mg protein LDL, respectively).  Inhibiton of LDL oxidation in M. nemestrina macrophage were highest by curcuminoid at 8 ppm for 4 hours and 6 hours incubation.  There was 14.8% and 23% inhibiton (P<0.01) (23.768 ± 0.095A vs 27.111B±0.972 and 23.37B±0.12 vs 30.87A±2.49 nmol/mg LDL protein, respectively).  These data suggest that curcuminoid of temu mangga were able to inhibit LDL oxidation in the cellular level, therefore offer protection against oxidation of LDL.   Key words: LDL, atherosclerosis, curcuminoid, Curcuma mangga